Employee Engagement : a key to Retention in the ITES Sector in India - Mishra, Leena (2013)
The aim of the project is to identify the nature of employee engagement practices in the ITES sector and how it aids in retention of employees and determines the causes for high attrition ITES in India. In this project we would look into the context within which the ITES industry has been growing in India and will be finding out factors for employee engagement in ITES industry in India. We would be using the questionnaire & Interview method and the sample size for the research would be 10 respondents from the ABC Company. The respondents are to be selected from Delhi and NCR. The findings would include various factors for employee engagement and retention practice in ITES. The study provides an insight about the various factors for the high turnover in ITES in India. The study has not only describes the magnitude of the problem present in the industry but also has provided information about the various practices that can help in reducing the high turnover. The finding would include the various reasons for Employee engagement and retention in ITES. In the finding we came across various reasons for the attrition like stress, better pay, career advancement and odd working hours. The different reasons are further seen against voluntary & non voluntary reasons for attrition. The project contains suggestions to which companies should pay attention towards why employees feel disappointed and to identify the needs of employee at most. This identification of reasons and needs would help companies to reduce cost of hiring new talents and the training cost. Implementing various suggestions would help companies retain the talent of human capital and the experience of the employees. Finally we would point out few recommendations for companies which would help companies in reducing the high attrition rates.